North Atlantic–Norwegian Sea exchanges during the past 135,000 years: Evidence from foraminiferal ∆14C, d11B, d18O, d13C, Mg/Ca, and Cd/Ca - Ezat, Mohamed M. (UiT Norges arktiske universitet, 2015)
The ocean is an essential regulator of climate through its effect on redistribution of heat and air-sea exchange of greenhouse gases.The modern circulation pattern of surface and deep water between the Arctic Mediterranean seas and North Atlantic is an important part of the global meridional ocean circulation. In this study we investigate the North Atlantic-Norwegian Sea exchanges of heat and carbon in connection to the glacial and deglacial climatic anomalies and carbon cycle evolution. During the last glacial and deglacial periods, abrupt and large amplitude switches in the northern hemisphere climate, particularly over Greenland, from cold (stadials) to warmer conditions (interstadials) were recorded. On the basis of isotopic and elemental composition of the fossil shells of planktic and benthic foraminifera, we assess the evolution in the seawater temperature, salinity, pH, CO 2 concentration, nutrient levels and 14 C ventilation ages from the southern Norwegian Sea. Our results show that the Norwegian Sea hydrography and it exchange with the North Atlantic changed in pace with past changes in regional climate, suggesting an important role. For instance, we show that the intermediate water in the Norwegian Sea has warmed-up by 2-5 °C during the cold stadials relative to the Holocene and interstadials. This subsurface build-up of heat during the cold stadials may have destabilized the water column, melted sea ice and ice shelves and thus significantly contributed to the onset of interstadial conditions. Our data show that glacial pH was elevated by ~0.2 units in the shallow subsurface Norwegian Sea compared to the Holocene. Brief episodes of acidification during some Heinrich stadials were recorded. Our results of intermediate water ventilation enabled us to evaluate and partly reject a suggestive hypothesis that the Nordic seas may have been a pathway for the mid-depth deglacial ∆ 14 C anomalies recorded in North Atlantic.